The sero-conversion of the people of the Nelson Mandela metropole, 1985-2021 - R.C.H. Shell; P. Rama (Contree, 2005)
The authors draw attention to the little researched pandemic of HIV/AIDS in the Western area of the Eastern Cape, South Africa. They use population projection programs and new historical case level data which has a broader base than the national ante natal clinic (anc) data. They demonstrate the utility of the component method for projecting urban population trends as opposed to commonly used mathematical (exponential or logistic) projections. While there is much more work involved in an urban component projection because of problems of recovering reliable in-migration data, the final product of the component projection are of such value to planners that it is suggested that all South African city planners could benefit from such projections. This study also attempts to establish that if the HIV pandemic is allowed to run unchecked, the total population of the Nelson Mandela Metropole will be just under two million people by the year 2021. Without Aids it would be between 2.5 and 4 million. The authors analyze the new data with a view to understand the probable historical vectors of the pandemic and to enable policy formulation, interventions and planning. Any attempt to forecast the course of an urban HIV pandemic is fraught with difficulties and uncertainties. These relate primarily to the number of assumptions which must be made in building forecasting models, often with historical data that is not reliable. The results of any model should therefore be treated with caution and must be used responsibly. That uncertainty, however, should not deter attempts at developing realistic forecasts for the future course of the HIV/AIDS pandemic at the urban level, since these local projections are essential in attracting and recruiting the attention of the stakeholder urban planners and managers who need to understand the possible impact of this disease on their communities, and to plan appropriately.